Modern weapons and military equipment for the issue 1-2024 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Japan’s long in development medium-caliber electromagnetic railgun could offer a huge boost in point d This Is A Ramjet Artillery Shell Right As It’s Fired Out Of A Howitzer; B-21 ‘Family Of Systems’ Details Emerge, Engine Test Runs Start; NATO has followed the U.S. Air Force in opting for the E-7A Wedgetail AEW&C aircraft as a partial replacement for its aging E-3 AWACS fleet.